Using local-spin k -exclusion algorithms to improve wait-free object implementations - Anderson, James H.; Moir, Mark (Distributed computing, 1997)
We present the first shared-memory algorithms for k-exclusion in which all process blocking is achieved through the use of 'local-spin' busy waiting. Such algorithms are designed to reduce interconnect traffic, which is important for good performance. Our k-exclusion algorithms are starvation-free, and are designed to be fast in the absence of contention, and to exhibit scalable performance as contention rises. In contrast, all previous starvation-free k-exclusion algorithms require unrealistic operations or generate excessive interconnect traffic under contention. We also show that efficient, starvation-free k-exclusion algorithms can be used to reduce the time and space overhead associated with existing wait-free shared object implementations, while still providing some resilience to delays and failures. The resulting 'hybrid' object implementations combine the advantages of local-spin spin locks, which perform well in the absence of process delays (caused, for example, by preemptions), and wait-free algorithms, which effectively tolerate such delays. We present performance results that confirm that this k-exclusion-based technique can improve the performance of existing wait-free shared object implementations. These results also show that lock-based implementations can be susceptible to severe performance degradation under multiprogramming, while our hybrid implementations are not.